STATUS PESANTREN MU’ADALAH; Antara Pembebasan dan Pengebirian Jatidiri Pendidikan Pesantren - Umar Bukhory (Institut Agama Islam Negeri Madura)
AbstractIslamic boarding school is the oldest Islamic education institution in Indonesia. from the perspective of politic, the existency of Islamic boarding school has just been admitted by the post-reformation government. It is declared on the article of UU No. 20 Tahun 2003 about SISDIKNAS, the establishment of special directorate in Religious Affairs departement, the publishment of various law products, and mu’âdalah (equality) toward some Islamic boarding schools. This article describes the problem of independecy and the diversity of Islamic boarding school educational systems after the publishment of the law products. undangan tersebut.Kata-kata kuncimu’adalah, pondok pesantren, pembaharuan kependidikan pesantren